2014
DOI: 10.1007/s11111-014-0210-7
|View full text |Cite
|
Sign up to set email alerts
|

Empirical research on international environmental migration: a systematic review

Abstract: This paper presents the findings of a systematic review of scholarly publications that report empirical findings from studies of environmentally-related international migration. There exists a small, but growing accumulation of empirical studies that consider environmentally-linked migration that spans international borders. These studies provide useful evidence for scholars and policymakers in understanding how environmental factors interact with political, economic and social factors to influence migration b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 63 publications
3
88
0
3
Order By: Relevance
“…A growing number of research works have been investigating the consequences on migration of short-, medium-, and long-term climate variability using different econometric approaches [49]. Several conflicting results can be found in the literature highlighting how climate-induced migration is a complex phenomenon, which depends on a variety of specific socio-economic conditions [50].…”
Section: Migration As a Coping Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of research works have been investigating the consequences on migration of short-, medium-, and long-term climate variability using different econometric approaches [49]. Several conflicting results can be found in the literature highlighting how climate-induced migration is a complex phenomenon, which depends on a variety of specific socio-economic conditions [50].…”
Section: Migration As a Coping Strategymentioning
confidence: 99%
“…A systematic review on the empirical findings obtained by studies investigating the international migration dimension of climate change can be found in [50]. Here the authors call attention to the important role played by the specific context under scrutiny in shaping environmental migration at the international level.…”
Section: Climate Change and International Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature would also benefit from more systematic transdisciplinary empirical approaches, and a widespread use of mixed quantitative and qualitative methods (Obokata et al, 2014;Piguet, 2010;Warner, 2011a, b).…”
Section: Discussionmentioning
confidence: 99%
“…There is a broad consensus that climate change will affect human migration in different ways (Adger et al, 2014;Black et al, 2011;Foresight, 2011;Ionesco et al, 2017;Obokata et al, 2014;Piguet, 2012;Tacoli, 2009;Warner and Afifi, 2014). Substantial evidence suggests that planning for and facilitation of migration can reduce future costs and increase human security (Adams and Adger, 2013;Adger et al, 2014;Ionesco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%